Analysis of the response to high temperature stress in hybrid grouper (Epinephelus fuscoguttatus♀×E. lanceolatus♂) - Hu, Yan; Tan, Yafeng; Liu, Junchi; Tang, Haizhan; Wang, Kaiwang; Tang, Feng; Luo, Jian; Wen, Xin (Frontiers in Marine Science, 2024)
Hybrid grouper (Epinephelus fuscoguttatus♀ × Epinephelus lanceolatus♂) are an essential species in marine aquaculture. However, they are susceptible to high temperatures, which can reduce disease resistance, slow growth rates, and decrease production efficiency, resulting in significant economic losses. This study aims to investigate the differences in heat tolerance between hybrid grouper and their parental species, tiger grouper (Epinephelus fuscoguttatus) and giant grouper (E. lanceolatus), and to identify heat stress-related signaling pathways and key genes. Through controlled temperature experiments, we measured the physiological and biochemical parameters of serum (ACP, AKP, TG, COR) and liver (HSP70, HSP90, SOD, CAT) in pearl gentian grouper and their parents, followed by liver transcriptome analysis of the three grouper species. The results showed that the lethal temperature of tiger grouper is 41℃, and the lethal temperature of hybrid tiger grouper and saddle grouper is 40 ℃ . Significant changes in antioxidant and heat stress-related indicators were observed in the early stages of stress. Comparative analysis of DEGs related to heat tolerance between pearl gentian grouper and their parents revealed common DEGs including the hsp family, danaj family, slc family, pnpla2, magot, actalb, and prodh. Among these, the gene expression trends in hybrids were similar to those of their maternal parent and varied between the same or opposite trends compared to those of their paternal parent. These findings suggest that the hybrids inherit heat regulation genes from both parents, with a higher proportion from the maternal parent, which likely explains their intermediate heat tolerance. This research provides insights into the potential relationship between heat tolerance in pearl gentian grouper and their parents and identifies key genetic information affecting heat tolerance.